2015
DOI: 10.1118/1.4923862
|View full text |Cite
|
Sign up to set email alerts
|

SU-D-304-03: Small Field Proton Dosimetry Using MicroDiamond and Gafchromic Film

Abstract: Purpose: Certain dosimetric characteristics continue to make proton beam therapy an appealing modality for cancer treatment. The proton Bragg peak allows for conformal radiation dose delivery to the target while reducing dose to normal tissue and organs. As field sizes become very small the benefit of the Bragg peak is diminished due to loss of transverse equilibrium along the central beam axis. Furthermore, aperture scattering contributes additional dose along the central axis. These factors warrant the need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Perturbations in output factor measurements of collimated fields have already been described in the past. Andersen et al 2 measured dose output in proton beams collimated with apertures between 5 and 100 mm using radiochromic film and a microDiamond detector, and found differences between both detectors of up to 70%. 2 Hoehr et al 12 identified differences in output factor measurements for collimated 74 MeV scattered proton fields down to 5 mm diameter.…”
Section: Proton Fields Combined With Collimatorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Perturbations in output factor measurements of collimated fields have already been described in the past. Andersen et al 2 measured dose output in proton beams collimated with apertures between 5 and 100 mm using radiochromic film and a microDiamond detector, and found differences between both detectors of up to 70%. 2 Hoehr et al 12 identified differences in output factor measurements for collimated 74 MeV scattered proton fields down to 5 mm diameter.…”
Section: Proton Fields Combined With Collimatorsmentioning
confidence: 99%
“…Andersen et al 2 measured dose output in proton beams collimated with apertures between 5 and 100 mm using radiochromic film and a microDiamond detector, and found differences between both detectors of up to 70%. 2 Hoehr et al 12 identified differences in output factor measurements for collimated 74 MeV scattered proton fields down to 5 mm diameter. Their investigation included a scintillation detector, a diamond detector oriented perpendicular to the beam direction and a silicon diode detector, of which the latter had the largest crosssectional area of 2.65 mm × 2.65 mm and showed a relative signal difference of 2% for the smallest field size, which the authors attributed to larger volume averaging.…”
Section: Proton Fields Combined With Collimatorsmentioning
confidence: 99%
See 3 more Smart Citations